NEUROCOSMETICS: AN EXTENSIVE OVERVIEW - RAJAGOPAL, SANJAI; SIVANATHAN, GURUBARAN; MAHADEVASWAMY, GIRIDHARA; ANGAMUTHU, GOWTHAM; DHANDAPANI, NAGASAMY VENKATESH (International Journal of Applied Pharmaceutics, 2025)
The review on this fast-evolving field of neuro cosmetics, at the intersection of neuroscience and cosmetic science, has interestingly led to innovative skincare treatment approaches. The paper progresses from a basic discovery of neurogenic inflammation made by substance P in 1996 the more recent skin-brain axis of 2015 to its applications. The review focuses on neurotransmitters such as acetylcholine and serotonin, neuropeptides such as substance P and Calcitonin Gene-Related Peptide (CGRP), and the neuroendocrine cells, Merkel, and Langerhans cells, to achieve skin homeostasis, inflammation control, and aging. The article looks at neurocosmetic applications such as anti-aging, skin barrier enhancement, and pigmentation management to active ingredients such as acetyl hexapeptide-8, niacinamide, and cannabidiol. Also reviewed are delivery systems including nanoencapsulation, microneedle technology, and iontophoresis in enhancing bioavailability and penetration of neuroactive compounds. A meta-analysis of clinical trials is shown. One study, which lasted up to 24 w, registered a 27% decrease in wrinkles and an 18% increase in elasticity with the peptide complex; the second one described a 45% decrease in rosacea erythema with Alpha-Melanocyte Stimulating Hormone (α-MSH) and Transient Receptor Potential Vanilloid (TRPV1) antagonists. In this review, emerging areas for future research are AI-driven personalized neurocosmetics, interventions of the gut-brain-skin axis, chronocosmetics, epigenetic modulation, smart nanocarriers, and bioelectronic skin therapies. Safety and regulatory issues that arise are commented on, emphasizing long-term studies and standardized approaches. The review is apt for any researcher or dermatologist looking for a comprehensive overview of how neurocosmetics hold transformative promise in topical peptide formulations.